Decentralization and Integration of Advanced Cardiac Care for the World's Poorest Billion Through the PEN-Plus Strategy for Severe Chronic Non-Communicable Disease - Sheila L. Klassen; Emmy Okello; Jose M. E. Ferrer; Faraz Alizadeh; Prebo Barango; Pilly Chillo; Yamikani Chimalizeni; Wubaye Walelgne Dagnaw; Jean-Luc Eiselé; Lauren Eberly; Anu Gomanju; Neil Gupta; et al. (Ubiquity Press, 2024)
Rheumatic and congenital heart disease, cardiomyopathies, and hypertensive heart disease are major causes of suffering and death in low- and lower middle-income countries (LLMICs), where the world's poorest billion people reside. Advanced cardiac care in these counties is still predominantly provided by specialists at urban tertiary centers, and is largely inaccessible to the rural poor. This situation is due to critical shortages in diagnostics, medications, and trained healthcare workers. The Package of Essential NCD Interventions - Plus (PEN-Plus) is an integrated care model for severe chronic noncommunicable diseases (NCDs) that aims to decentralize services and increase access. PEN-Plus strategies are being initiated by a growing number of LLMICs. We describe how PEN-Plus addresses the need for advanced cardiac care and discuss how a global group of cardiac organizations are working through the PEN-Plus Cardiac expert group to promote a shared operational strategy for management of severe cardiac disease in high-poverty settings.